PENCEGAHAN STUNTING PADA ANAK DALAM PERSPEKTIF HINDU DI DESA BANGKAL KECAMATAN SERUYAN RAYA KABUPATEN SERUYAN - sarma, nyoman -; Juni Arta, I Gede Arya; Etika, Tiwi; Vedanti, Kunti Ayu; Gayatri, Kamisriati Levi (Fakultas Dharma Duta dan Brahma Widya, 2024)
Stunting prevention is one of the priorities for the Indonesian government to ensure that the nation's next generation can grow well and healthily. Stunting generally occurs due to a lack of nutritional intake in children, which causes growth to be disrupted and abnormal. This can be physically observed from the child's weight and height which are not ideal for their growing age. In the long term, stunting can even cause various disorders such as decreased thinking power, and can cause chronic diseases. The participation of all components is needed to solve this problem, so a multi-disciplinary study is very necessary. This research is a field study or field research, which was carried out using a qualitative descriptive approach. Primary data was obtained through interviews with sources determined using the purposive sampling method. The aim of this research is to conduct a study of the problem of stunting among children in Bangkal Village, Seruyan Raya District, Seruyan Regency from a Hindu religious perspective. Based on the research that has been carried out, several things can be found: first, the community in Bangkal Village, Seruyan Raya District, Seruyan Regency perceives stunting in terms of beliefs and traditions, apart from being a medical problem. Second, the implementation of Hindu religious teachings in Bangkal Village, Seruyan Raya District, Seruyan Regency as an effort to prevent stunting is carried out through ceremonies for babies in the womb and after birth called nahunan in accordance with the guidance of the Veda and the Panaturan book. Third, the implications of Hindu religious teachings for preventing stunting in children in Bangkal Village, Seruyan Raya District, Seruyan Regency are: the philosophical implications of the yadnya ceremony, the philosophical implications of the 3, 7 and 9 month pregnancy ceremonies, and the philosophical implications of the nahunan ceremony.